Activation of Gold on Metal Carbides: Novel Catalysts for C1 Chemistry - Rodriguez, José A. (Frontiers in Chemistry, 2020)
This article presents a review of recent uses of Au-carbide interfaces as catalysts for C1 Chemistry (CO oxidation, low-temperature water-gas shift and CO2 hydrogenation). The results of density-functional calculations and photoemission point to important electronic perturbations when small two-dimensional clusters of gold are bounded to the (001) surface of various transition metal carbides (TiC, ZrC, VC, Ta C and δ-MoC). On these surfaces, the C sites exhibited strong interactions with the gold clusters. On the carbide surfaces, the Au interacts stronger than on oxides opening the door for strong metal-support interactions. So far, most of the experimental studies with well-defined systems have been focused on the Au/TiC, Au/ δ-MoC and Au/beta-Mo2C interfaces. Au/TiC and Au/ δ-MoC are active and stable catalysts for the low-temperature water-gas shift reaction and for the hydrogenation of CO2 to methanol or CO. Variations in the behavior of the Au/δ-MoC and Au/beta-Mo2C systems clearly show the strong effect of the metal/carbon ratio on the performance of the carbide catalysts. This parameter substantially impacts the chemical behavior of the carbide and its interaction with supported metals, up to the point of modifying the reaction rate and mechanism of C1 processes.